c.1 - Sibal, Rajni Sekhri (Gurgaon, 2009)
The hand book comprises of detailed guidelines on how to conduct an effective inspection and review, and also provides checklists which have been drawn up in a focused manner to ensure that a comprehensive inspection is conducted.
Keywords: Inspection